Oxidative mafic rock weathering through geological time - Babechuk, Michael G. (Trinity College (Dublin, Ireland). Department of Geology, 2015)
Oxidative chemical weathering requires the presence of free oxygen in the Earth's atmosphere. Reconstructing the terrestrial oxidation history in the ancient rock record has helped to detect the intrinsic links between atmospheric composition and biological evolution of oxygenic photosynthesis. This thesis contributes to this theme via the study of oxidative chemical weathering at different stages of Earth's history and at different weathering intensities. It presents detailed geochemical investigations of three profiles developed on mafic rock. Laterite (Bidar) and saprolite (Chhindwara) profiles hosted on Deccan Traps basalt (India) capture weathering in the Phanerozoic, while the ca. 1.85 Ga Flin Flon paleosol (Canada) hosted on greenstone captures weathering after the Great Oxidation Event (GOE, ca. 2.4-2.3 Ga).
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin.